Phenotypic, biochemical and genomic variability in generations of the rapeseed (Brassica napus L.) mutant lines obtained via chemical mutagenesis. - Alexandra V Amosova; Svyatoslav A Zoshchuk; Valentina T Volovik; Anna V Shirokova; Nickolai E Horuzhiy; Galina V Mozgova; Olga Yu Yurkevich; Margarita A Artyukhova; Valentina A Lemesh; Tatiana E Samatadze; Olga V Muravenko (PLoS ONE, 2019)
The phenotypic, biochemical and genetic variability was studied in M2-M5 generations of ethyl methansulfonat (EMS, 0.2%) mutagenized rapeseed lines generated from canola, '00', B. napus cv. Vikros. EMS mutagenesis induced extensive diversity in morphological and agronomic traits among mutant progeny resulted in selection of EMS populations of B. napus- and B. rapa-morphotypes. The seeds of the obtained mutant lines were high-protein, low in oil and stabilized in contents of main fatty acids which make them useful for feed production. Despite the increased level of various meiotic abnormalities revealed in EMS populations, comparative karyotype analysis and FISH-based visualization of 45S and 5S rDNA indicated a high level of karyotypic stability in M2-M5 plants, and therefore, the obtained mutant lines could be useful in further rapeseed improvement. The revealed structural chromosomal reorganizations in karyotypes of several plants of B. rapa-type indicate that rapeseed breeding by chemical mutagenesis can result in cytogenetic instability in the mutant progeny, and therefore, it should include the karyotype examination. Our findings demonstrate that EMS at low concentrations has great potential in rapeseed improvement.